Advanced quantitative magnetic resonance imaging of lower extremity muscle microtrauma after marathon: a mini review - Cheng, Yu; Li, Xiaokai (Frontiers in Sports and Active Living, 2024)
This article reviews the existing literature and outlines recent advances in quantitative Magnetic Resonance Imaging (MRI) techniques for the assessment of lower extremity muscle microtrauma following a marathon. Single-modality quantitative MRI techniques include T2 mapping to assess the dynamics of muscle inflammatory edema and variability at the site of injury, Diffusion Tensor Imaging (DTI) to detect subclinical changes in muscle injury, Intravoxel Incoherent Motion (IVIM) imaging to provide simultaneous information on perfusion and diffusion in muscle tissue without the need for intravenous contrast, and Magnetic Resonance Spectroscopy (MRS) to noninvasively detect intramyocellular lipid (IMCL) content in muscle before and after marathon exercise to explain the use of fatty acids as an energy source in skeletal muscle during long-distance running. As well as Chemical Exchange Saturation Transfer (CEST) is particularly suitable for detecting changes in free creatine, pH values and lactate concentrations in muscles before and after exercise, providing a more detailed picture of muscle physiology and chemistry. These metabolic MRI methods enhance the understanding of biochemical alterations occurring in muscles pre-and post-exercise. Multimodal techniques combine different modalities to provide a comprehensive evaluation of muscle structural and functional changes. These advanced techniques aim to better assess microtrauma and guide clinical treatment, though further validation with larger studies is needed to establish their potential over traditional qualitative methods.